Progress and Regress of Time Dependent Data and Application in Bank Branch - F. Hosseinzadeh Lotfi; Z. Taeb; S. Abbasbandy (Journal of Applied Mathematics)
To evaluate each decision making unit having time dependent inputs and outputs data, a new method has been developed and reported here. This method uses the Malmquist productivity index, and is a very simple function based on Cubic Spline function to determine the progress and regress of that unit. To show the capability of this developed method, the data of 9 branches of a commercial bank has been used, evaluated, and reported.